Listed family firms in Europe: Relevance, characteristics and performance - Aleksandra Gregorič; Marc Steffen Rapp; Ignacio Requejo (Foundation for Family Businesses, 2022)
Publicly traded family businesses in Europe do business with a longer-term perspective and more successfully than companies that are not family businesses – and the greater the influence of the founding family, the better their performance. This is the conclusion reached by the study of an international research team directed by Dr. Marc Steffen Rapp, Professor of Economics at the Philipps-Universität Marburg. – – Die börsennotierten Familienunternehmen in Europa wirtschaften langfristiger und erfolgreicher als Nicht-Familienunternehmen. Die Performance ist umso besser, je größer der Einfluss der Gründerfamilie. Das zeigt eine Studie eines internationalen Forscherteams unter der Leitung von Prof. Dr. Marc Steffen Rapp, Professor für Betriebswirtschaftslehre an der Universität Marburg.
Keywords: 330; Familienunternehmen; Aktiengesellschaft; Unternehmenserfolg; EU-Staaten; Schweiz; Norwegen